Razvojni izzivi Slovenije - Nared, Janez; Perko, Drago (Regionalni razvoj, 2009)
This book ('Slovenia's development challenges') deals with fundamental issues of Slovenia's development. It explains the main issues in Slovenia's Development Strategy, and evaluates its bases and the direct effects of individual development measures. Each in their own way, the authors discuss pressing developmental issues at the level of the state, regions, municipalities, or individual sectors, seeking possible answers, new stimulation, potentials, and opportunities. The basic premise was that the main task is to seek solutions for an economically successful, socially just, environmentally friendly, and ethically responsible society, and that all development efforts must focus on these goals. Although it was adopted only three years ago, in line with the premises described above and the changed macroeconomic conditions, Slovenia's Development Strategy requires amendments to turn Slovenia's development path in a sustainably more acceptable direction. One should not be guided only by a desire for quantity~instead, one should strive for higher-quality development that is fair to every citizen as well as the environment.